Diagnosis of Schistosoma infection in non-human animal hosts: A systematic review and meta-analysis. - Song Liang; Keerati Ponpetch; Yi-Biao Zhou; Jiagang Guo; Berhanu Erko; J Russell Stothard; M Hassan Murad; Xiao-Nong Zhou; Fadjar Satrija; Joanne P Webster; Justin V Remais; Jürg Utzinger; et al. (PLoS Neglected Tropical Diseases)
Background Reliable and field-applicable diagnosis of schistosome infections in non-human animals is important for surveillance, control, and verification of interruption of human schistosomiasis transmission. This study aimed to summarize uses of available diagnostic techniques through a systematic review and meta-analysis. Methodology and principal findings We systematically searched the literature and reports comparing two or more diagnostic tests in non-human animals for schistosome infection. Out of 4,909 articles and reports screened, 19 met our inclusion criteria, four of which were considered in the meta-analysis. A total of 14 techniques (parasitologic, immunologic, and molecular) and nine types of non-human animals were involved in the studies. Notably, four studies compared parasitologic tests (miracidium hatching test (MHT), Kato-Katz (KK), the Danish Bilharziasis Laboratory technique (DBL), and formalin-ethyl acetate sedimentation-digestion (FEA-SD)) with quantitative polymerase chain reaction (qPCR), and sensitivity estimates (using qPCR as the reference) were extracted and included in the meta-analyses, showing significant heterogeneity across studies and animal hosts. The pooled estimate of sensitivity was 0.21 (95% confidence interval (CI): 0.03-0.48) with FEA-SD showing highest sensitivity (0.89, 95% CI: 0.65-1.00). Conclusions/significance Our findings suggest that the parasitologic technique FEA-SD and the molecular technique qPCR are the most promising techniques for schistosome diagnosis in non-human animal hosts. Future studies are needed for validation and standardization of the techniques for real-world field applications.